Comparison of the epidemiological and clinical fingerprints of Human Granulocytotropic Anaplasmosis and Human Monocytotropic Ehrlichiosis in the United States - Christian Kositz; Larissa Gygax; Sophie Schudel; Esther Kuenzli; Andreas Neumayr (PLoS ONE, 2025)
Background Human granulocytotropic anaplasmosis (HGA), caused by Anaplasma phagocytophilum, and human monocytotropic ehrlichiosis (HME), caused by Ehrlichia chaffeensis , are tick-borne zoonoses. The vast majority of Anaplasma phagocytophilum infections reported worldwide are from the United States. Ehrlichia chaffeensis infections are reported exclusively from North America, with the majority reported from the United States. We have recently summarized the available data on HGA and HME in the form of two systematic reviews. We compared data from these two systematic reviews to objectify differences in epidemiological and clinical presentation between the two diseases in the United States. Methods From our recently published systematic reviews on HGA and HME, «best evidence data» were extracted and comparatively analyzed. Cases were included if (i) they had a high level of diagnostic certainty (i.e., diagnosed by PCR, culture, immunostaining of tissue, or paired IgG IFA serology), (ii) individual clinical data were available, (iii) no concomitantly present coinfection(s) were reported, and (iv) the infection was acquired in the United States. Results HME cases were statistically more frequent immunocompromised and younger and had gastrointestinal symptoms, hepatosplenomegaly and elevated liver function tests (LFT) levels. HGA cases were statistically more frequent presenting with pulmonary symptoms and encephalitis. Hospitalization and a fatal outcome was more frequent in HME. No differences in fatal outcome were observed between immunocompetent and immunocompromised HME cases. Conclusion Although HGA and HME show similarities, there are statistically significant differences in terms of their clinical patterns and outcomes and a not yet described difference in the affected age pattern.